2018
DOI: 10.2196/resprot.8348
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Internet-Based Behavioral Intervention to Improve Psychosocial Health Outcomes in Children With Insomnia (Better Nights, Better Days): Protocol for a Randomized Controlled Trial

Abstract: The author-made SQ is a screening instrument comprised of 12 items to assess whether participants meet study inclusion criteria and do not meet any of the exclusion criteria. A specific item addressing co-sleeping is modelled conceptually on Ramos and colleagues' [63] study examining parental perceptions of sleep problems. The questionnaire requires approximately 5 minutes to complete. Eligibility Measures Behavioural Insomnia Questionnaire (BIQ)The BIQ is adapted by the authors based on the insomnia diagnosis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 109 publications
0
25
0
Order By: Relevance
“…This study included parents of children, now aged 4–14 years, who previously met research criteria for insomnia and participated in the BNBD pan-Canadian RCT 3.5 years prior ( Corkum et al, 2018 ). All parents who consented to participate in the BNBD RCT and consented to be contacted for future research ( n = 524) were eligible to participate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study included parents of children, now aged 4–14 years, who previously met research criteria for insomnia and participated in the BNBD pan-Canadian RCT 3.5 years prior ( Corkum et al, 2018 ). All parents who consented to participate in the BNBD RCT and consented to be contacted for future research ( n = 524) were eligible to participate.…”
Section: Methodsmentioning
confidence: 99%
“…This intervention offered evidence-based strategies for establishing a bedtime routine, creating a healthy sleep environment, stress reduction techniques, learning to fall asleep independently (i.e., modified extinction-based strategies), and using a reward system. Conducting a mixed-methods follow-up study with this cohort provided an opportunity to understand sleep during the first wave of the COVID-19 pandemic in children who had well-characterized sleep concerns and a comprehensive assessment of relevant psychosocial variables prior to the pandemic ( Corkum et al, 2018 ). An explanatory sequential mixed-methods approach was taken, a method by which quantitative data are collected and explored in-depth using qualitative data ( Creswell & Plano Clark, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, web-based interventions are also gaining popularity in light of their relative success. [55][56][57] A Committee focused on Practice Parameters from the American Academy of Sleep Medicine reviewed 52 treatment studies pertaining to behavioral treatments of pediatric insomnia. They found that 94% of studies showed clinically significant improvements in the context of behavioral interventions.…”
Section: Treatmentmentioning
confidence: 99%
“…AYAs are drawn to technology; therefore, technology provides an opportunity to directly reach this large invisible at-risk cohort for whom sleep disorders contribute to psychopathology and vice versa [ 34 , 35 ]. Although there are web-based programs for infant (aged 6-36 months) [ 36 ], pediatric (aged 1-8 years) [ 37 , 38 ], adolescent [ 39 - 41 ], and adult sleep disturbances [ 42 ], there are no evidence-based transdiagnostic programs that adequately address the multitude of sleep problems observed in AYAs and that span both adolescence and young adulthood. Put differently, as some of the sleep problems of AYAs are unique and go beyond insomnia (eg, voluntary sleep restriction, circadian phase delay, and poor sleep hygiene), pediatric and adult programs are not suitable for this age group.…”
Section: Introductionmentioning
confidence: 99%